2016
DOI: 10.7324/japs.2016.601225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pattern, Severity and Outcome of Poisoning in Emergency Care Unit

Abstract: The current study was a prospective observational study. All poisoning cases admitted in the emergency care unit of M.S. Ramaiah Hospital and Memorial Hospital were included in the study. A total of 101 patients were included in the study. The pattern, severity and outcome of poison case were assessed using suitable scales. The common agent involved in poisoning was drugs. It accounted for 38.60% of total poisoning cases. This was followed by organophosphorous (OP) compounds, corrosive agents, rat poison, bedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 2 publications
4
20
1
Order By: Relevance
“…The proper treatment with antidote may remarkably neutralize the toxic action of the poison and increase its elimination. Our findings were similar to other studies conducted [13][14][15][16] Atropine and PAM were commonly administered by parenteral routes in those patients among insecticide poisoning consumed the organophosphorus compound. Hence, atropine competitively antagonizes muscarinic effects of those compounds and PAM reactivates cholinesterase enzyme.…”
Section: Resultssupporting
confidence: 92%
“…The proper treatment with antidote may remarkably neutralize the toxic action of the poison and increase its elimination. Our findings were similar to other studies conducted [13][14][15][16] Atropine and PAM were commonly administered by parenteral routes in those patients among insecticide poisoning consumed the organophosphorus compound. Hence, atropine competitively antagonizes muscarinic effects of those compounds and PAM reactivates cholinesterase enzyme.…”
Section: Resultssupporting
confidence: 92%
“…Our study showed that Organophosphorus poisoning was the fi rst cause (55%) while paracetamol poisoning 15% was the second cause which indicated the similarity in the other study. Suicidal manner (87.5%) of poisoning is more common than the accidental and homicidal pattern in our study and the result are similar to the other stud 1,9,10 . Family disputes, unemployment problem and stress in the profession may be the contributing factors for committing suicide for both male and female.…”
Section: Vijay Mate From South India Observed Thatsupporting
confidence: 91%
“…In this study younger patients were significantly observed as the majority of the poisoning cases ranged in the age groups ≤3 0 y (57.89%). A pattern similar to this has been reported in Indian studies [14,15]. As young adults progress through generations, their traditional households generally get less supportive of their choices pertaining to financial social sectors, marriage age, premarital sex, rehabilitation, stress in academics as well as inability in achieving the targets in professional and educational fronts [16].…”
Section: Discussionsupporting
confidence: 72%